Sudan : Second Review Under the 2009-10 Staff-Monitored Program-Staff Report; Staff Supplement; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report, 2011)
Economic growth is estimated to have moderated further in 2010 to about 5 percent, reflecting slower growth in both the oil and non-oil sectors. The overall commitment fiscal deficit for 2010 is now estimated at 2.7 percent of GDP, about 0.6 percentage point of GDP below the program target. Monetary policy was expansionary in the first half of 2010, but was subsequently tightened. The current account deficit narrowed during the first three quarters of 2010 largely driven by an increase in oil exports.